Fabrication, electrical and optical properties of silver, indium tin oxide (ITO), and indium zinc oxide (IZO) nanostructure arrays. Issue 5 (17th April 2013) - Khosroabadi, Akram A.; Gangopadhyay, Palash; Duong, Binh; Thomas, Jayan; Sigdel, Ajaya K.; Berry, Joseph J.; Gennett, Thomas; Peyghambarian, N.; Norwood, Robert A.
Abstract In thin film devices such as light‐emitting diodes, photovoltaic cells and field‐effect transistors, the processes of charge injection, charge transport, charge recombination, separation and collection are critical to performance. Most of these processes are relevant to nanoscale metal and metal oxide electrode–organic material interfacial phenomena. In this report we present a unique method for creating tailored one‐dimensional nanostructured silver, tin and/or zinc substituted indium oxide electrode structures over large areas. The method allows production of high aspect ratio nanoscale structures with feature sizes below 100 nm and a large range of dimensional tunability. We observed that both the electronic and optical properties of these electrodes are closely correlated to the nanostructure dimensions and can be easily tuned by control of the feature size. Surface area enhancement accurately describes the conductivity studies, while nanostructure dependent optical properties highlight the quasi‐plasmonic nature of the electrodes. Optimization of the nanostructured electrode transparency and conductivity for specific opto‐electronic systems is expected to provide improvement in device performance. <inline-graphic xlink:href="ark:/27927/pgg20q11w3d" content-type="pssa201329129-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />